Current development of bovine jugular vein conduit for right ventricular outflow tract reconstruction - Li, Chenggang; Xie, Bo; Tan, Ruizhe; Liang, Lijin; Peng, Zhaoxiang; Chen, Qi (Frontiers in Bioengineering and Biotechnology, 2022)
Right ventricular outflow tract (RVOT) reconstruction is a common surgical method to treat congenital cardiac lesions, and bovine jugular vein conduit (BJVC) has become a prevalent candidate of prosthetic material for this procedure since 1999. Although many clinical studies have shown encouraging results on BJVCs, complications such as stenosis, aneurysmal dilatation, valve insufficiency, and infective endocarditis revealed in other clinical outcomes still remain problematic. This review describes the underlying mechanisms causing respective complications, and summarizes the current technological development that may address those causative factors. Novel crosslinking agents, decellularization techniques, conduit coatings, and physical reinforcement materials have improved the performances of BJVCs. The authors expect that the breakthroughs in the clinical application of BJVC may come from new genetic research findings and advanced characterization apparatuses and bioreactors, and are optimistic that the BJVC will in the future provide sophisticated therapies for next-generation RVOT reconstruction.